2014
DOI: 10.1016/j.yjmcc.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Low dystrophin levels in heart can delay heart failure in mdx mice

Abstract: Duchenne muscular dystrophy is caused by mutations that prevent synthesis of functional dystrophin. All patients develop dilated cardiomyopathy. Promising therapeutic approaches are underway that successfully restore dystrophin expression in skeletal muscle. However, their efficiency in the heart is limited. Improved quality and function of only skeletal muscle potentially accelerate the development of cardiomyopathy. Our study aimed to elucidate which dystrophin levels in the heart are required to prevent or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…A study in genetically modified mice suggests that expression in 3 to 5% of cardiomyocytes at the wild-type level (in every dystrophin positive cell) may delay the onset of heart disease [21]. In a different study, Wu et al found that 5% dystrophin positive cells in the heart of adult mdx mice did not improve cardiac histology/baseline function although mice tolerated dobutamine stress better [22].…”
Section: Introductionmentioning
confidence: 99%
“…A study in genetically modified mice suggests that expression in 3 to 5% of cardiomyocytes at the wild-type level (in every dystrophin positive cell) may delay the onset of heart disease [21]. In a different study, Wu et al found that 5% dystrophin positive cells in the heart of adult mdx mice did not improve cardiac histology/baseline function although mice tolerated dobutamine stress better [22].…”
Section: Introductionmentioning
confidence: 99%
“…We show that programmable CRISPR complexes can be delivered locally and systemically to terminally differentiated skeletal muscle fibers and cardiomyocytes, as well as muscle satellite cells, in neonatal and adult mice, where they mediate targeted gene modification, restore DYSTROPHIN expression and partially recover functional deficiencies of dystrophic muscle. As prior studies in mice and humans indicate that DYSTROPHIN levels as low as 3–15% of wild-type are sufficient to ameliorate pathologic symptoms in the heart and skeletal muscle (2326), and levels as low as 30% can suppress the dystrophic phenotype altogether (27) and protect dystrophic muscle from damage (28), the restoration of DYSTROPHIN achieved here by one-time administration of AAV- Dmd CRISPR clearly encourages further evaluation and optimization of this system as a new candidate modality for the treatment of DMD (see Supplementary Text). …”
mentioning
confidence: 99%
“…It has been estimated that even low-level expression of dystrophin (4 to 15%) can partially ameliorate cardiomyopathy (24) and protect against eccentric contraction-induced injury in skeletal muscle (25). The efficiency of restoration of dystrophin expression observed after delivery of Myoediting components to mdx mice by AAV is therefore within the range expected to provide therapeutic benefit.…”
mentioning
confidence: 99%